DETERMINAN KESEJAHTERAAN PETANI TANAMAN PANGAN DI PROVINSI ACEH TAHUN 2012-2017 - Akram Akramur Rasyid; Budyanra Budyanra (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2018)
AbstractThe economy in Aceh Province is heavily dependent on agriculture, especially agricultural-cropswhich absorb the largest workforce of 29.68 percent and contribute the second largest grossdomestic product (GDP) after industrial sector by 13.14 percent in 2017 and increase year toyear. However, the absorption of agricultural manpower especially large agricultural-crops is notbalanced with farmers' welfare level when viewed from NTPP which is still below 100 value. Thisresearch aims to know the development of welfare level of agricultural-crop farmer and othervariables, variables that affect it. In this research, the welfare level of agricultural-crop farmers isapproached with NTPP variable as dependent variable, while independent variables used are drypaddy harvest price, rice seed price, grain transport cost, and NTPP of previous period. The datasource is from the Badan Pusat Statistik (BPS) in 2012-2017 monthly. This research usesdescriptive analysis and time series data regression analysis. The results showed that the variablesof dry harvested paddy price, NTPP of the previous period were significantly positive, and theprice of paddy seed was negatively significant to NTPP current period in the long run. In the shortterm the price of dry grain harvest and NTPP of the previous period was significantly positive forNTPP current period. The results of this study recommend to the government in maintaining thestability of the rice seed price by subsidizing the good quality of rice seeds to farmers andmaintaining the stability of the dry paddy harvest price by determining the Government PurchasePrice (GPP) according to the harvest time.Keywords: Farmers’ welfare, agricultural-crops, dry paddy harvest price, rice seed price, graintransport cost, time series data regression.AbstrakPerekonomian di Provinsi Aceh sangat bergantung dengan sektor pertanian khususnya tanamanpangan yang mampu menyerap tenaga kerja terbesar yaitu 29,68 persen dan memberikankontribusi produk domestik bruto (PDB) kedua terbesar setelah sektor industri sebesar 13,14persen tahun 2017 dan meningkat dari tahun ke tahun. Namun, penyerapan tenaga kerja sektorpertanian khususnya tanaman pangan yang besar tersebut tidak diimbangi dengan tingkatkesejahteraan petani bila dilihat dari NTPP (Nilai Tukar Petani Tanaman Pangan) yang masihberada dibawah nilai 100. Penelitian ini bertujuan untuk mengetahui perkembangan tingkatkesejahteraan petani tanaman pangan dan variabel-variabel yang memengaruhinya. Pada penelitianini tingkat kesejahteraan petani tanaman pangan didekati dengan variabel NTPP sebagai variabeldependen, sedangkan variabel independen yang digunakan adalah harga gabah kering panen, hargabenih padi, ongkos angkut gabah, dan NTPP bulan sebelumnya. Penelitian ini menggunakananalisis deskriptif dan analisis regresi data time series. Hasil penelitian menunjukkan bahwavariabel harga gabah kering panen, NTPP bulan sebelumnya signifikan positif, dan harga benihpadi signifikan negatif terhadap NTPP bulan sekarang pada jangka panjang. Pada jangka pendekharga gabah kering panen dan NTPP bulan sebelumnya signifikan positif terhadap NTPP bulansekarang. hasil penelitian ini merekomendasikan kepada pemerintah dalam menjaga kestabilanharga benih padi dengan memberikan subsidi benih padi yang berkualitas kepada para petani danmenjaga kestabilan harga gabah kering panen dengan menentukan harga pembelian pemerintah(HPP) sesuai masa panen.